2018
DOI: 10.1021/acs.est.8b04956
|View full text |Cite
|
Sign up to set email alerts
|

A Microcosm Study of Surface Sediment Environmental DNA: Decay Observation, Abundance Estimation, and Fragment Length Comparison

Abstract: Interpretation of environmental DNA (eDNA) is a major problem hindering the application of this emerging technology for environmental monitoring. The decay characteristics and bioabundance estimation of different DNA fragment lengths are largely unknown, especially for eDNA captured from surface sediments. An estuarine amphipod, Grandidierella japonica, was used as the target species in this study. We conducted a lab-scale experiment using DNA extraction to clarify the effect of bacteria on eDNA decay. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 44 publications
5
42
0
Order By: Relevance
“…In another word, the resolution of surface sediment eDNA was more than one month based on the results obtained from this study. It was also consistent with our previous kinetic study [37] of eDNA which pointed out that eDNA from surface sediment has the potential to indicate the water environment at a certain present temporal scale.…”
Section: Variation Of Edna Copy Numbersupporting
confidence: 92%
“…In another word, the resolution of surface sediment eDNA was more than one month based on the results obtained from this study. It was also consistent with our previous kinetic study [37] of eDNA which pointed out that eDNA from surface sediment has the potential to indicate the water environment at a certain present temporal scale.…”
Section: Variation Of Edna Copy Numbersupporting
confidence: 92%
“…Therefore, the estimation of abundance by using eDNA metabarcoding needs careful interpretation. Wei et al (2018) observed two phases in the sedimentary eDNA decay process: a fast-decay phase (until 72 hr after removal of individuals), followed by a slow-decay phase (until 480 hr). However, we F I G U R E 5 Number of fish species detected by eDNA metabarcoding.…”
Section: Ta B L Ementioning
confidence: 98%
“…Most eDNA studies on macro-organisms analyzed eDNA in water samples (Goldberg, Strickler, & Fremier, 2018;Ishige et al, 2017;Minamoto et al, 2012;Miya et al, 2015;Ushio et al, 2018;Valentini et al, 2016); however, several recent studies have targeted eDNA in underwater sediments (Buxton, Groombridge, & Griffiths, 2018;Shaw et al, 2016;Turner, Uy, & Everhart, 2015;Wei, Nakajima, & Tobino, 2018). To date, comparison of the basic properties between sample types (i.e., water/sediment) has been performed only for fish eDNA.…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer studies measuring eDNA decay or degradation in sediment, but Sakata et al [54] also found lower rates of decay in sediment than in water, with rates in sediment even a magnitude lower than our findings (k = 0.0003) for two fish species. Interactive factors that affect rates have been identified, including biochemical oxygen demand and initial concentration of eDNA present [21] and bacterial activity [55], as well as protection from other adverse conditions (e.g., enzymatic degradation by binding to clay or organic fractions) [22,56]. Sediment has been long recognized for its protective characteristics that extend survival of microbes [22,53].…”
Section: Plos Onementioning
confidence: 99%